Visibility analysis of the urbanistic environmet as a constituent of the urbogeosystems approach - Kostrikov , Sergiy; Serohin, Denys; Berezhnoy, Vitaliy (Human Geography Journal, 2021)
This paper recognizes the conceptual approach to the visual analysis of an urbogeosystem (VA UGS), which is within the Urban Studies domain. This approach stays within Human Geography frameworks and based on visibility estimation in the urbanistic environment (UE). The definition of UE is represented as a 3D-formalized model of an actual city environment (CE). In general, our work is a further development of the methodological urbogeosystem concept once introduced by one of this paper’s authors. This concept has been previously explained as a twofold functional entity, which is a base for delineation and analysis of the CE urbogeosystemic properties. The basic possibility of VA UGS has been explained as a possibility, that follows from the circumstance, according to which UE is a quasi-rasterized model of a continual nature of an actual city space and its key features. Then, this model of city continuality can be contrasted with the discrete nature of an urbogeosystem – a hierarchical aggregate of urban features. Exactly this contraposition (continuality versus discrete content) provides the basics for the visual analysis.This research introduces the Visibility Hemisphere concept (VHC), what supposes those conditions of visibility, which do correspond to ambient optic array ones. The Line of Sight (LoS) has been represented as a significant VHC component. Transformation of 2D LoS into 3D-segment of Visibility Hemisphere has been briefly explained within the stereometric frameworks. A number of formalized parameters have been introduced on the base of VHC. Computation of these parameters is the first stage of VA UGS introduction. The introduced approach has been further implemented as the VA-functionality of a web-GIS-application and illustrated with a few interface samples. Visual analysis of Munster-city UGS (Germany) has been provided within this research as a use-case of three scenarios comparative estimation of urban environment developed changes. Possible negative visual impact has been evaluated for each of the scenarios.